Noorsche mythen uit de Edda's en de sagen / door H. A. Guerber ; bew. door H. W. Ph. E. v.d. Bergh van Eysinga - Guerber, H. A ; Eysinga, H. W. Ph. E. v.d. Bergh van (Thieme, 1920)
xv, 389 halaman : ilustrasi ; 23 cm